Question

Use the METHOD of REDUCTION OF ORDER to find the general solution of the differential equation...

Use the METHOD of REDUCTION OF ORDER to find the general solution of the differential equation y"-4y=2 given that y1=e^-2x is a solution for the associated differential equation. When solving, use y=y1u and w=u'.

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
Use the method of reduction of order to find the general solution of the following differential...
Use the method of reduction of order to find the general solution of the following differential equation. (t^2) d^2y/dt^2 + t dy/dt + (t^2-1/4) y = 0, y1(t) = sin t/sqrt(t)
Follow the steps below to use the method of reduction of order to find a second...
Follow the steps below to use the method of reduction of order to find a second solution y2 given the following differential equation and y1, which solves the given homogeneous equation: xy" + y' = 0; y1 = ln(x) Step #1: Let y2 = uy1, for u = u(x), and find y'2 and y"2. Step #2: Plug y'2 and y"2 into the differential equation and simplify. Step #3: Use w = u' to transform your previous answer into a linear...
The indicated function y1(x) is a solution of the associated homogeneous differential equation. Use the method...
The indicated function y1(x) is a solution of the associated homogeneous differential equation. Use the method of reduction of order to find a second solution y2(x) and a particular solution of the given nonhomoegeneous equation. y'' − y'  = e^x y1 = e^x
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order...
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order or formula (5) in Section 4.2, y2 = y1(x) e−∫P(x) dx y 2 1 (x) dx     (5) as instructed, to find a second solution y2(x). y'' + 36y = 0;    y1 = cos(6x) y2 = 2) The indicated function y1(x) is a solution of the given differential equation. Use reduction of order or formula (5) in Section 4.2, y2 = y1(x) e−∫P(x) dx y 2 1...
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order,...
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order, to find a second solution dx **Please do not solve this via the formula--please use the REDUCTION METHOD ONLY. y2(x)= ?? Given: y'' + 2y' + y = 0;    y1 = xe−x
Use the provided solution and reduction of order to find the general solution to the following...
Use the provided solution and reduction of order to find the general solution to the following differential equation. x^(2)y''-6xy'+12y=0 y1(x)=x^4
Use the method of undetirmined coefficients to find the general solution of the differential equation y''+4y'-5y...
Use the method of undetirmined coefficients to find the general solution of the differential equation y''+4y'-5y = 5cos(2x)
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order...
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order or formula (5) in Section 4.2, y2 = y1(x) e−∫P(x) dx y 2 1 (x) dx        (5) as instructed, to find a second solution y2(x). y'' + 64y = 0;    y1 = cos(8x) y2 =
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order...
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order or formula (5) in Section 4.2, y2 = y1(x) ∫(e(−∫P(x) dx))/y12(x)dx (5) as instructed, to find a second solution y2(x).4x2y'' + y = 0; y1 = x1/2 ln(x) y2 = ?
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order...
The indicated function y1(x) is a solution of the given differential equation. Use reduction of order or formula (5) in Section 4.2, y2 = y1(x) e−∫P(x) dx y 2 1 (x)       dx (5) as instructed, to find a second solution y2(x). x2y'' -11xy' + 36y = 0; y1 = x6 y2 =